1.3.1. Hydrothermal Synthesis, Crystal Structure and Fluorescent Property of a New Three-Dimensional Cd(II) Coordination Polymer Based on 1,3-Bis(imidazol-1- ylmethyl)-benzene (Communications in Inorganic Synthesis, 2015)
Abstract: A new cadmium(II) coordination polymer, namely[Cd(mbix)3]n·2nClO4 (mbix = 1,3-bis(imidazol-1-ylmethyl)benzene) (1), has been prepared and fully characterized by single-crystal X-ray diffraction, elemental analyses, IR spectroscopyand luminescent property. Of the compound, the Cd(II)center is octahedral coordinated with mbix serving as a bridgingligand by employing six N-donor to coordinate with the Cd(II)center. It exbihits three-dimensional network structure via mbixligands.Supporting information: X-Ray (CIF file).